2011
DOI: 10.1038/cr.2011.174
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Exogenous plant MIR168a specifically targets mammalian LDLRAP1: evidence of cross-kingdom regulation by microRNA

Abstract: In the initial published version of this article, an error was made during the assembly of Figure 5B. Figure 5B is a representative image of western blots, which shows that rice-derived MIR168a can down-regulate LDLRAP1 expression in mouse liver and that the injection of antiMIR168a rescued the expression of LDLRAP1. After the initial publishing of this article, it has been brought to our attention that the image of the internal control in previous Figure 5B showing the western blot results of α-tubulin, actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Zhang and other researchers demonstrated the cross-kingdom interaction concept, in which miRNA present in plant extracts introduced by the diet were able to control gene expression in human cells (16,43,44). More recently, we have sequenced the miRnome of Moringa oleifera , and miRNA homologous to human miRNA was identified (12,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and other researchers demonstrated the cross-kingdom interaction concept, in which miRNA present in plant extracts introduced by the diet were able to control gene expression in human cells (16,43,44). More recently, we have sequenced the miRnome of Moringa oleifera , and miRNA homologous to human miRNA was identified (12,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, scientific studies have demonstrated the existence of a so-called ‘cross-kingdom interaction’, which is mediated by exogenous miRNAs that are derived from plants: These, inside the host cell, serve to regulate the gene expression machinery (1216).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled feeding study to corroborate Zhang et al (2011) Analysis of plasma and liver did not reveal measurable uptake of rice miRNAs…”
Section: Plant-and Pollen-derived Mirnasmentioning
confidence: 96%
“…Being an important regulator of gene expression, miRNAs were implicated in numerous biological and pathological processes, such as inflammation, tumor metastasis, intestinal microbiota regulation, and immune system regulation, often through interspecies communications. For example, miR-168a from rice entered the serum through gastrointestinal tract in mice and inhibited the expression of low-density-lipoprotein receptor adapter protein 1, thereby decreasing the level of low-density lipoprotein . However, the concept of dietary transfer of miRNAs was subjected to intense debate as to whether a cross-kingdom effect existed or whether these exogenous miRNA detected in blood and tissues were reflective of sample contamination or nonfunctional ingestion. Although some studies showed that miRNAs in plant ELNs and milk EVs presented within the human circulatory system followed dietary intake and exerted their specific biological functions via cross-species/cross-kingdom regulation of endogenous target gene expression, corroborating and proverbial evidence were still needed to support their direct regulatory role in consumers.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%